Sustainable kids fashion: designers’ viewpoint toward multifunctional children’s wear design - Jalil, Marzie Hatef; Shaari, Nazlina (Universiti Putra Malaysia, 2023)
Fast-fashion products encourage parents to spend more on their children’s necessities. Children’s clothing is one of the vast parts of post-consumer waste due to the children’s growing fast. This study is intended to investigate multifunctional childrenswear among clothing designers to reduce children’s clothing waste by the following sustainability. According to the multifunctional design concept, children’s clothing is used for multifunctional purposes and recycled and decomposed at the end of the clothing’s lifespan. This research is adapted to a mix- method strategy. An in-depth interview was accepted to analyse the multifunctional children’s clothing. Moreover, a survey was conducted to collect data on designers’ viewpoints to design multifunctional children’s clothing. It was found that the sustainable practice, environmental knowledge, social and market environment, and multifunctional clothing properties signiﬁcantly affected the designer’s viewpoint to design such clothes. However, health issues influence the designer’s standpoint. The ﬁnding showed that giving awareness of multifunctional children’s clothing products among designers would help to improve the acceptance of such clothes. The consequences of this study can be analysed from an educational and managerial standpoint to establish an effective strategy for increasing the rate of sustainability in children’s clothing and developing policies to promote multifunctional clothing design.